Associations Between Community Health Worker Capacity and Stunting Reduction Efforts in South Central Timor, Indonesia - Riny Pujiyanti; Irfan Irfan; Fitri Handayani; Simon Sani Kleden; Norma Tiku Kambuno; Maria Hilaria; Oluebube Magnificient Eziefule (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Malnutrition, particularly childhood stunting, remains a critical issue in Indonesia, including the South-Central Timor (SCT) District, East Nusa Tenggara Province. Stunting affects 149.2 million children under five years globally. In the SCT District (2025), stunting prevalence reached 41%. Climatic conditions, food insecurity, and cultural factors contribute to this problem. Prevention efforts involve national strategies, including behavioral change communication campaigns, with Community Health Workers (CHWs) playing crucial roles due to their community credibility and responsiveness. CHW participation is voluntary without continuous commitment obligations. CHW activity and roles in stunting reduction acceleration are paramount, necessitating the investigation of influencing factors. This study aims to identify the factors associated with the roles of Community Health Workers (CHWs) in accelerating stunting reduction in the SCT District in 2025. Methods: This quantitative cross-sectional study included 124 CHWs from 10 community health centers in the SCT District. The study was conducted from January to May 2025. Separate questionnaires measured each variable (CHW role, knowledge, and skills). Ethical approval was obtained from the Kupang Health Polytechnic Research Ethics Committee. Results: Bivariate analysis revealed that knowledge level, education, training history, work duration (all p<0.001), and CHW skills (p=0.002) were significantly associated with CHW roles. The final model showed training history increased CHW role effectiveness by 45.3 times (OR=45.354; 95% CI=1.634-1258.56), CHW skills by 44.3 times (OR=44.393; 95% CI=2.721-724.36), and work duration by 16.9 times (OR=16.934; 95% CI=1.280-224.02). Conclusion: Training, skill level, and work duration were associated with higher CHW role performance, supporting improved stunting prevention efforts. This study provides a new understanding of the importance of enhancing CHW knowledge and skills through structured/routine training programs. Further research comparing CHW capacity in low versus high stunting areas is important for understanding CHW capacity management program improvements.